Field measurement of the organic peroxy radicals by the low-pressure reactor plus laser-induced fluorescence spectroscopy - SL Li; Lu, K. D.; Ma, XF; XP Yang; SY Chen; Zhang, Y. H. (Chinese Chemical Letters, 2020)
A low-pressure reactor (LPR) was developed for the measurement of ambient organic peroxy (RO2) radicals with the use of the laser-induced fluorescence (LIF) instrument. The reactor converts all the ROx (= RO2 + HO2 + RO + OH) radicals into HO2 radicals. It can conduct different measurement modes through altering the reagent gases, achieving the speciated measurement of RO2 and RO2# (RO2 radicals derived from the long-chain alkane, alkene and aromatic hydrocarbon). An example of field measurement results was given, with a maximum concentration of 1.88 x 10(8) molecule/cm(3) for RO2 and 1.18 x 10(8) molecule/cm(3) for RO2#. Also, this instrument quantifies the local ozone production rates directly, which can help to deduce the regional ozone control strategy from an experimental perspective. The new device can serve as a potent tool for both the exploration of frontier chemistry and the diagnosis of the control strategies. (C) 2020 Chinese Chemical Society and Institute of Materia Medica, Chinese Academy of Medical Sciences. Published by Elsevier B.V. All rights reserved.
Keywords: atmospheric chemistry; chemical amplifier; field observation; flow tube reactor; ho2; lif; matrix-isolation; north china plain; oh; organic peroxy radicals; ozone production rate; ro2; ro2 measurement; rural site